2016
DOI: 10.7554/elife.10820
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane chemokines act as receptors in a novel mechanism termed inverse signaling

Abstract: The transmembrane chemokines CX3CL1/fractalkine and CXCL16 are widely expressed in different types of tumors, often without an appropriate expression of their classical receptors. We observed that receptor-negative cancer cells could be stimulated by the soluble chemokines. Searching for alternative receptors we detected that all cells expressing or transfected with transmembrane chemokine ligands bound the soluble chemokines with high affinity and responded by phosphorylation of intracellular kinases, enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 49 publications
1
43
0
Order By: Relevance
“…Additionally, in accordance with our recent findings in gliomas [10], application of a specific CXCL16 antibody (αCXCL16) which may also induce the intrinsic activity of tm- CXCL16, resulted in phosphorylation of both Akt and ERK1/2 (Fig. 2b, right side) after 20 min.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Additionally, in accordance with our recent findings in gliomas [10], application of a specific CXCL16 antibody (αCXCL16) which may also induce the intrinsic activity of tm- CXCL16, resulted in phosphorylation of both Akt and ERK1/2 (Fig. 2b, right side) after 20 min.…”
Section: Resultssupporting
confidence: 92%
“…Thereby, we verified this new mechanism beside its appearance in malignant glioma cells [10] in a different system, and showed that “inverse signaling” seems to be a broad biological process as it is also observable in more benign tumor cells.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations